Implementation of effective teaching based on Islamic educational psychology in early childhood - Nur Ain Safiah; Ain Sholehah Suhada; Nur Amaliya Aika Rosli; Nurul Ismiah (Edusoshum : Journal of Islamic Education and Social Humanities, 2025)
This research aims to identify and analyze effective teaching strategies based on Islamic educational psychology for early childhood, in order to address the lack of integration of Islamic values in education. This study is a qualitative literature review examining literature related to early childhood education from an Islamic perspective. The results show that the implementation of effective teaching must consider child developmental psychology, divided into three stages: the infant and toddler stage (0-3 years) focusing on the values of monotheism and sensory stimulation; the preschool stage (3-6 years) emphasizing the formation of morals through play-based learning and Islamic stories; and the transition stage (5-6 years) with approaches such as learning the Qur'an and prayers, as well as the development of Islamic character. With appropriate teaching methods, children can develop holistically, encompassing cognitive, emotional, social, and spiritual aspects.